2021
DOI: 10.2147/oaem.s291510
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Motorcycle Accidents and Its Associated Factors Among Road Traffic Accident Patients in Hawassa University Comprehensive Specialized Hospital, 2019

Abstract: Background: Road traffic damages were amongst the central causes of passing away, hospitalization, disability, and low socioeconomic status. About 1.3 million lethal road traffic damages and 20-50 million nonfatal damages happened consequently of road traffic accidents every year globally. Motorcycles are a small subsection of all motor vehicles significantly over-represented in total motor vehicle accidents and lead to a great rate of deaths and disabilities. Objective: The study aimed to assess the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
(19 reference statements)
4
13
2
Order By: Relevance
“…Drivers who had driven on non-asphalted road types had three times higher odds of being involved in traffic accidents on the road than drivers who had driven on asphalted road types. This result aligns with a result reported in Hawassa, Ethiopia (27), which might be due to similarities in the geography of the study area. The road features are, in turn, determined by natural topography, the quality of roads by themselves, the absence of roadside traffic signals, and the absence of speed breakers, especially on sloppy roads.…”
Section: Discussionsupporting
confidence: 91%
“…Drivers who had driven on non-asphalted road types had three times higher odds of being involved in traffic accidents on the road than drivers who had driven on asphalted road types. This result aligns with a result reported in Hawassa, Ethiopia (27), which might be due to similarities in the geography of the study area. The road features are, in turn, determined by natural topography, the quality of roads by themselves, the absence of roadside traffic signals, and the absence of speed breakers, especially on sloppy roads.…”
Section: Discussionsupporting
confidence: 91%
“…The elderly demonstrated some defensive driving behaviors, such as slowing down when entering an intersection and never changing lanes without signaling. This is in contrast to research by Antin et al, who found that elderly drivers commonly failed to switch on their turn signal before starting a lane change [15] but these are consistent with safe driving practices as studies found that the usage of sensors on the steering wheel raises drivers' attention span [16] and high speed was significantly associated with motorcycle accidents [ 17] . However, this study revealed that older people still had inappropriate behaviors, including not having a motorcycle driver's license when driving, overtaking on the wrong side (the left), and riding a motorcycle with more than one passenger.…”
Section: Discussioncontrasting
confidence: 80%
“…Our paper is connected to a growing literature investigating the factors linked with road trafc crashes [21][22][23][24][25][26][27][28][29]. According to a Nigerian study of 224 commercial motorcyclists, 46% have been involved in at least one trafc accident.…”
Section: Introductionmentioning
confidence: 91%